Quality of Life and Mid-Term Survival of Patients Bridged with Extracorporeal Membrane Oxygenation to Left Ventricular Assist Device. Issue 3 (May 2017) - Unai, Shinya; Yamane, Kentaro; Tanaka, Daizo; Cook, Gary; Hirose, Hitoshi; Cavarocchi, Nicholas C.; Entwistle, John W. C.
Abstract : Insertion of a left ventricular assist device (LVAD) improves survival and quality of life (QOL) in patients with class IV heart failure failing medical management. However, QOL and survival of patients bridged to LVAD with extracorporeal membrane oxygenation (ECMO) is unknown. Between July 2008 and June 2014, 213 patients underwent insertion of HeartMate II LVAD at two VAD centers without a bridge with a temporary VAD. Extracorporeal membrane oxygenation was used as a bridge before LVAD insertion in 22 Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) 1 patients (ECMO-VAD group). No bridge was used in 21 INTERMACS 1 patients and 170 INTERMACS 2–4 patients (primary LVAD group). Survival was compared between the ECMO-VAD group and INTERMACS 1 patients who underwent a primary LVAD insertion (INTERMACS 1 group). Quality of life was compared between the ECMO-VAD group and the primary LVAD group as a whole. The in-hospital mortality of the ECMO-VAD and INTERMACS1 groups was 23% and 14%, respectively ( P = 0.38). The postimplant QOL scores of the ECMO-VAD group were not different compared with the primary LVAD group. Although the ECMO-VAD group consists of critically ill patients, the QOL and survival after discharge were not significantly different compared with patients who were not bridged with ECMO.